ADOPTION AND ADAPTATION: DIACHRONIC PERSPECTIVES ON THE GROWING SOPHISTICATION OF SOCIAL MEDIA USES IN ELECTIONS CAMPAIGNS - Larsson, Anders Olof; Bruns, Axel; Highfield, Tim; Stromer-Galley, Jennifer; Kenski, Kate; Hemsley, Jeff; Bryant, Lauren; Xiu, Huichuan; Semaan, Bryan; Rossi, Luca; Giglietto, Fabio (AoIR Selected Papers of Internet Research, 2015)
Much like the Internet itself during the mid-1990s, social media such as Twitter and Facebook have now become standard tools in a number of professional contexts. In doing so, they have undergone gradual processes of adoption and adaptation, as their potential uses are explored, evaluated, and revised over time, and as the insights gained by early adopters are disseminated to other potential users. But because of the slow and incremental nature of such adoption and adaptation processes, they are often overlooked by social media research which examines single cases and phenomena. Such tendencies are perhaps most evident in relation to the study of political elections: here, the effective use of social media by the successful Obama campaign in the 2008 US presidential election is often positioned as an obvious starting point for mainstream political uses of contemporary social media platforms such as Facebook and Twitter, creating the impression that its strategies emerged fully formed rather than themselves building on the lessons learnt from previous campaigns, and that subsequent campaigns merely needed to copy Obama’s successful formula in their own electioneering efforts (e.g Miller, 2013). Such simplistic perspectives overlook, however, that each election campaign proceeds from its own underlying factors (such as the persona of the candidate and their position in the polls) and that the idiosyncratic US electoral system diverges vastly from those of most other parliamentary democracies (thus requiring very different campaigning styles). What worked for Obama - campaigning for direct election in a two-person content where voting is voluntary - is unlikely to work in a multi-party system whose leaders are indirectly elected and where voting is compulsory, for example (e.g. Gibson & McAllister, 2014). There is, therefore, a significant need for research into social media campaigning strategies not only in, but also beyond the US context, and over the past years AoIR and other conferences have already seen a substantial number of such studies being presented. However, the bulk of research into these issues has continued to be designed as single-country or single-election case studies, providing useful findings but lacking a longitudinal, diachronic, or comparative perspective that would be able to trace any developmental trends in political social media use between or during elections. This panel seeks to remedy this dearth of research by featuring several diachronic approaches to the study of online political communication during elections, and by thus enabling a comparative perspective on the gradual adoption and adaptation of social media for political campaigning across a range of national contexts. Specifically, the panel presents research into the political uses of social media for campaigning in four different countries: Australia, Sweden, the USA, and Italy. In combination, these four presentations provide an overview over a diverse range of contexts, and offer new insights into the ways that electoral and political systems as well as the current political standing of key parties and candidates affect the evolution of social media campaigning strategies.